Portraits of Labor Market Exclusion - Sundaram, Ramya (Washington, DC: World Bank, 2014)
The financial crisis that hit the global market in the middle of 2008 gave way to the sharpest contraction of the European economies since the Great Depression. In 2009 the economic output in the countries of the European Union shrank 4.5 percent, the largest reduction in GDP since its creation. Since then, the economies have slowly recovered, but unemployment has continued to rise, reaching 11 percent in 2013, up from 7.1 percent in 2008. The economy of the European Union shrank 4.5 percent, the largest reduction in its GDP since the Union s creation. Furthermore, for the European Union as a whole, long-term unemployment among 15- to 64-year-olds has increased from 37.2 percent in 2008 to 47.5 percent of total unemployment in 2013. In several countries more than half of those unemployed are long-term unemployed, that is, they have been looking for jobs for more than 12 months. In Greece and Bulgaria the share of long-term unemployed in 2013 was 67.5 percent and 57.3 percent, respectively. Youth unemployment, on the other hand, has increased almost 8 percent since 2008, reaching 23.3 percent in 2013 in the EU-28 countries. In Bulgaria, Romania and Hungary, around a fourth of 15- to 24-year-olds are unemployed; in Greece close to 60 percent of youth were unemployed in 2013. Long spells of unemployment expose individuals to impoverishment. They can also lead to deterioration of skills and detachment from the labor market. Youth unemployment is particularly concerning as it risks damaging longer-term employment prospects for young people, leading them to face higher risks of exclusion and poverty. Youth unemployment also has growth implications as a generation of educated and productive people are not working at their potential. Finally, very high levels of youth unemployment for long periods of time can become a threat to social stability.